(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Employment and job creation is one of the most pressing issues. This article analyzes the newly created and reduced jobs created by legal entities in terms of organizational legal form. Based on the results of the analysis, ways to provide the population with sustainable jobs are proposed.